Relayout of oxygen filling area with seven waste method and green manufacturing analysis - Haryudiniarti, Ayu Nurul; Samsudin, Samsudin; Restuasih, Sinta Restuasih (Universitas Sultan Ageng Tirtayasa, 2023)
PT MM aims to enhance efficiency in filling oxygen gas and reduce transportation routes by employing forklifts. They have reconfigured the company's oxygen gas supply area by eliminating damaged machines and relocating the functional ones to a new area. The proposed solution for the company involves redesigning the layout of the laser cutting machine area and optimizing it using the seven-waste method. The re-layout procedure comprises three steps: analyzing the initial layout, designing alternative layouts based on Lean Manufacturing principles, and evaluating and selecting the best layout. The alternative layout results in improved material handling efficiency and reduced transportation distances. The outcomes of this redesign included the removal of the MCP storage area, which was replaced by a minibulk and a pipe installation that connects the minibulk to each laser cutting machine. By eliminating the 20-meter square MCP tube storage area, forklift mileage in the laser cutting machine area was significantly reduced. Overall, these changes led to a 30% reduction in costs, calculated from the difference between monthly rental costs and usage costs. This initiative supports green manufacturing by decreasing Nox emissions through reduced forklift usage.